(3TQM OjhGf Rjf GdYGHOjf Ydi Hf GdMSjfs - (3Rjf GdYGHOjf , Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH GdgGTej, CHh GdMSf,J (B94 (3g` s
(3ChdgG (B:s
(3JHGQc Ph GdYdG hGdcHQjGA JaQO HGdLdGd hGdHbGA s
(3BNQgG (B:s
(3heMGYfg Rjf GdeYGUi ceG bGd Gddg JYGdi (B((3Ef GdMSfGJ jPgHf GdSjFGJ(B) (3GdMeO ddg JeJ s
(3GdOjhGf eQJH Ydi GdbhGais
(3GdSLGO gh Rjf GdYGHOjf Ydi Hf GdMSjfi Hf Ydi Hf CHj WGdH GdeJhai (B94(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs